ANALISIS IMPLEMENTASI JUAL BELI SISTEM PRE ORDER MENURUT FATWA DSN NO 05/DSN-MUI/IV/2000 TENTANG JUAL BELI SALAM (Studi Kasus Pada Pengrajin Batik Asad Kertijayan Pekalongan): Dibuat Oleh Nur Apriyanti, Sobrotul Imtikhanah, Moegiri - moegiri, moegiri; apriyanti, Nur; imtihanah, sobrotul (FEB Universitas Muhammadiyah Pekajangan Pekalongan, 2021)
This study aims to examine the suitability of the implementation of the pre–order buying and selling system (Salam) carried out by the entrepreneur or batik producer Asad Kertijayan Pekalongan based on Fatwa DSN NO 05/DSN-MUI/IV/2000 about “Salam” buying and selling system. It is a qualitative study with an observation and interview as a data collecting technique. The subject of this data was chosen by snowballing data. This system is customer orders batik from the Batik Asad Kertijayan Pekalongan. The buyer pays the full amount of money that has been determined as a sign of the contractin accordance with the goods ordered. Meanwhile, the seller will explain the specifications of the ordered goods, the type, the time and the place of delivery. About the implementation of pre – order buying and selling system (Salam) in Batik Asad Kertijayan Pekalonga, the provisions on payment, on goods, on delivery of goods and the provisions on the pillars and terms of sale and purchase of Salam in islam, based on Fatwa DSN NO 05/DSN-MUI/IV/2000, this system has been complied with the Fatwa. Keywords : Salam, buying and selling, the provisions of payment, the provisions of goods, the provisions of delivery.